Cell‐mediated BMP‐2 release from a novel dual‐drug delivery system promotes bone formation. Issue 12 (29th October 2013) - Liu, Tie; Wu, Gang; Zheng, Yuanna; Wismeijer, Daniel; Everts, Vincent; Liu, Yuelian
Abstract Objectives In this study, a novel biomimetic calcium phosphate bone substitute (BioCaP) is introduced as a dual‐drug release system with two drug/protein delivery modes: protein is incorporated into (i) the interior of BioCaP (an internal depot); and (ii) a superficial calcium phosphate coating on BioCaP (a surface‐coated depot). Our aim is to investigate each of the two delivery modes of BioCaP. Our hypotheses are that (i) both of the drug delivery modes, in in vitro as well as in vivo environment, can achieve a sustained cell‐mediated protein release; and (ii) BioCaP with these two delivery modes with incorporated bone morphogenetic protein‐2 (BMP‐2) promotes bone formation. Materials and Methods Tablets of BioCaP were prepared with different carrying modes using bovine serum albumin (BSA) as model protein. The release of this protein was analysed (n = 6 per group). Granules of BioCaP with different carrying modes of BMP‐2 were implanted subcutaneously in rats (n = 6 animals per group). Samples were collected after 5 weeks for histomorphometric analysis. Results In vitro data showed that the internal and surface‐coated depots of BSA resulted in a sustained osteoclast‐mediated release, while the adsorbed BSA was rapidly released, and this release was not affected by osteoclasts. In vivo data showed that the volume densities of bone, bone marrow, and blood vessels were significantly higher in samples where BMP‐2 was incorporated internally or in the coating compared with granules with adsorbed growth factor. Osteoclast‐like cells were associated with the granules, and resorption lacunae were frequently observed. Conclusion It is shown that different modes of incorporation of BMP‐2 on and in BioCaP granules have a beneficial effect on the formation of ectopic bone. This dual‐drug release system makes BioCaP granule a promising tool for delivering multiple therapeutic agents for different clinical applications.